PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PULP & KERTAS YANG TERDAFTAR DI BEI 2012 - 2019 - Ketrin Novelita Sinaga; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
Every research carried out has a purpose that underlies the research. Knowing the effect of Profitability and Company Size on Tax Avoidance in the pulp & paper sub sector is the main objective of this study. The number of sub-sector population used is 9 companies and has been selected through purposive sampling technique, so that the sample size becomes 4 companies with 8 years of financial reporting period and 32 samples are obtained. In this study, the results show that profitability has an effect on tax avoidance, firm size has no effect on tax avoidance.